The Mob: A Play in Four Acts - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Mob: A Play in Four Acts" by John Galsworthy is a dramatic work likely written in the early 20th century, addressing political and moral dilemmas during a time of conflict. The play centers around Stephen More, a Member of Parliament, who stands at a moral crossroads as he grapples with his conscience regarding a war and the ramifications it has on his family and society. The opening of the play introduces us to Stephen More's dining room, where heated discussions are unfolding among a group of characters, including his wife Katherine and various other family members and associates. The debate focuses on national honor and the ethics of engagement in warfare, highlighting the tensions between personal conviction and public duty. As More prepares to make a speech against the war, his firm stance garners anger from those around him, particularly from his wife, who pleads with him to reconsider given the familial repercussions of his choices. This sets the stage for a drama infused with societal critique, family loyalty, and the struggle for individual integrity amidst the clamor of the "mob." (This is an automatically generated summary.)
Release date is 2004-09-26
Produced by David Widger
Keywords: English drama